Greek cafés and milk bars of Australia - Alexakis, Effy; Janiszewski, Leonard (Braddon, A.C.T. : Halstead Press, 2016)
Nostalgic trip to the days when the Greek Cafe was the gathering place for every town and suburb. Effy Alexakis's evocative photos are paired with marvellous images from family albums. The cafes and the people behind them, showing decor, milkshakes, sundaes and innovative sweets were combined in a unique and special Australian experience. The authors have travelled Australia, Greece, Egypt and the USA, tracking down cafes, milk bars and their forerunners overseas.
Includes bibliographical references and index.
Keywords: Greeks -- Australia -- Social life and customs; Greek Australians -- Social life and customs; Coffee shops -- Australia -- History; Fast food restaurants -- Australia -- History; Australia -- Social conditions; Australian